Pengembangan Skala Psikologis Profil Pelajar Pancasila Bernalar Kritis Pada Fase D Sebagai Instrumen Asesmen Diagnostik Dalam Layanan Bk Berbasis Kurikulum Merdeka - Ratnawati, Vivi; Arofah, Laelatul; Puspitarini, Ikke Yuliani Dhian; Sunita, Lutfi Deva (Nusantara of Research : Jurnal Hasil-hasil Penelitian Universitas Nusantara PGRI Kediri, 2024)
The Pancasila student profile is the direction of education goals in Indonesia. There are six dimensions that must be mastered by students to become competent individuals, including 1) faith, devotion to God Almighty, and noble character, 2) independence, 3) mutual cooperation, 4) global diversity, 5) critical reasoning, and 6) creative. The purpose of this study is to develop a psychological scale of critical reasoning dimensions for the diagnostic assessment process of students in schools. There are five dimensions in critical reasoning, namely argumentation, assumption, deduction, interpretation, and conclusion. Meanwhile, the critical reasoning scale statement items totalled 44. This study adopted Gregory's development model using six steps, namely defining the test, selecting the scaling method, constructing the items, trialling the items, revising the test, and publishing the test. The results showed the acceptability of the critical reasoning scale, based on expert tests conducted on two experts from BK experts showed a score of 0.5. Further research is needed to improve the validity and reliability of the psychological scale that has been developed, perhaps through wider experimental tests or the development of supporting media.